2017
DOI: 10.1519/jsc.0000000000001564
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Gaelic Athletic Association 15 Training Program on Neuromuscular Outcomes in Gaelic Football and Hurling Players: A Randomized Cluster Trial

Abstract: O'Malley, E, Murphy, JC, McCarthy Persson, U, Gissane, C, and Blake, C. The effects of the Gaelic Athletic Association 15 training program on neuromuscular outcomes in Gaelic football and hurling players: A randomized cluster trial. J Strength Cond Res 31(8): 2119-2130, 2017-Team-based neuromuscular training programs for injury prevention have been tested primarily in female and adolescent athletes in soccer, handball, and basketball with limited research in adult male field sports. This study explored whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 37 publications
5
54
0
1
Order By: Relevance
“…One study 15 demonstrated changes in LESS scores for both groups, while three studies 14,16,17 demonstrated changes for the IPP groups only.…”
Section: Results Of Searchmentioning
confidence: 98%
See 4 more Smart Citations
“…One study 15 demonstrated changes in LESS scores for both groups, while three studies 14,16,17 demonstrated changes for the IPP groups only.…”
Section: Results Of Searchmentioning
confidence: 98%
“…• O'Malley et al 17 demonstrated improvements in LESS scores after participating in the IPP. Improvements in Y-balance test reach directions and composite scores were also identified.…”
Section: Results Of Searchmentioning
confidence: 99%
See 3 more Smart Citations